Symbolic Order Lacan pada Terbentuknya Identitas Masjid - Ema Dwi Arsita; Ema Yunita Titisari; Damayanti Asikin; A. Ghafar Ahmad (RUAS)
The Jami Adji Amir Hasanoeddin Mosque symbolizes the development of Islam in the Kingdom of Kutai Kartanegara, which was previously a Hindu kingdom. This research aims to expose the representation of the architectural identity of the Jami Adji Amir Hasanoeddin Mosque with the perspective of Lacan's identity theory, especially the symbolic order stage. This is important to do considering that the symbolic meaning of mosques now needs to be strengthened and re-contextualized in an increasingly globalized community culture, so it requires strengthening identity. This study uses a descriptive-qualitative approach. Historical data and data on the original state of the building were collected through observation, documentation, and interviews. The analysis process is carried out through a series of identification of the process of identity formation at the mirror stage and symbolic order through the interpretation of the relationship between observation units (history, mosque architectural elements, stakeholders, and related political elements). The results of the study show that the identity of the Jami Adji Amir Hasanoeddin Mosque is as a 'leader' or center for the development of Islam. This is shown by the choice of location, role, and function of the mosque both at the beginning of its existence until the reign of Aji Sultan Muhammad Parikesit, as well as efforts to embrace various social groups through the diversity of architectural elements.